THE ROLE OF THE MEDIA IN SHAPING PUBLIC PERCEPTIONS OF NARCOTICS TRAFFICKERS: A CASE STUDY OF DECISION NUMBER 1235/PID.SUS/2025/PN MDN - Arjuna; Halimatul Maryani (Jurnal Ilmu Hukum dan Keadilan, 2026)
This study aims to analyze the role of mass media in shaping public perceptions of drug dealers and its impact on the judicial process and judicial independence. The focus of the research is directed at mass media coverage of narcotics crime cases in Decision Number 1235/Pid.Sus/2025/PN Mdn, in which the defendant was sentenced to life imprisonment despite the public prosecutor demanding the death penalty. The findings indicate that mass media play a highly significant role in shaping public perceptions of drug dealers through mechanisms of framing and agenda setting. Media coverage, particularly that which emphasizes the large quantity of evidence and the disparity between the prosecutor’s demand and the judge’s decision, constructs a specific social reality that influences how the public understands narcotics cases. Such coverage has an indirect impact on the judicial process and perceptions of judicial independence. Although normatively and factually judges continue to render decisions based on the law and facts presented at trial, confrontational and sensational media framing has the potential to create moral pressure and affect public trust in judicial institutions. There is a correlation between the intensity and type of media framing and the level of public support for court decisions: the greater the intensity of coverage and the stronger the framing highlighting disparities between prosecutorial demands and judicial rulings, the greater the tendency for the public to be critical of or to reject judicial decisions. However, this correlation is social-communicative in nature and should not be interpreted as a causal relationship that binds judges in rendering their decisions.